2022
DOI: 10.3389/fneur.2022.824926
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Advances in Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is an autoimmune disease affecting the central nervous system that causes significant disability and healthcare burden. The treatment of MS has evolved over the past three decades with development of new, high efficacy disease modifying therapies targeting various mechanisms including immune modulation, immune cell suppression or depletion and enhanced immune cell sequestration. Emerging therapies include CNS-penetrant Bruton's tyrosine kinase inhibitors and autologous hematopoietic ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 152 publications
0
43
0
Order By: Relevance
“…Yet, as exemplified by MS, relapses and remission are treated distinctively, indicating that heterogeneous processes prevail at different stages of the disease. In fact, steroids and TPE are used to treat acute clinical deteriorations while disease modifying therapies (DMTs) are administered during remission to prevent further relapses [ 21 , 22 ]. Future studies should investigate the impact of anti-CD20 medications and TPE on cytokines and other inflammatory substances to determine the common denominator responsible for the treatment response of both therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, as exemplified by MS, relapses and remission are treated distinctively, indicating that heterogeneous processes prevail at different stages of the disease. In fact, steroids and TPE are used to treat acute clinical deteriorations while disease modifying therapies (DMTs) are administered during remission to prevent further relapses [ 21 , 22 ]. Future studies should investigate the impact of anti-CD20 medications and TPE on cytokines and other inflammatory substances to determine the common denominator responsible for the treatment response of both therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The MS pathogenesis is still under discussion, although it is known that there are confirmed risk factors, such as the presence of the allele HLA- DRB1*1501 in the MHC complex of affected subjects and environmental factors like vitamin D level, obesity, smoking, and the Epstein-Barr virus (EBV) infection [ 13 ].…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…DMTs for MS include immune modulators such as β-interferons, glatiramer acetate, teriflunomide, cladribine, natalizumab, and dimethyl fumarate; S1P receptor modulators, including fingolimod, ozanimod, siponimod, and ponesimod; and agents that deplete CD20+ B cells, including ocrelizumab and ofatumumab. 26 "Early on [in the pandemic]," explained Shin, "there was a concern that patients with MS might be extra vulnerable and that DMTs could increase vulnerability to COVID-19, particularly the categories of medicines that are perceived to be more immunosuppressive." This, Shin discussed, led to some prescribers delaying certain treatments at the start of the pandemic, although, in general, Shin reported that this is no longer occurring.…”
Section: Covid-19 Infection Sars-cov-2 Vaccinations and Disease Modif...mentioning
confidence: 99%